Characteristics And Causes of Work-Related Eye Trauma at Bekasi Regency Hospital - Anugrah, Andreas Surya; Ruhdiat, Rudi; Wadan, Angelicha Magdalena Slomen Kewa; Abrar, Ligadhea (Eduvest - Journal of Universal Studies, 2025)
Work-related eye trauma cases at Bekasi Regency Hospital were analyzed in a retrospective descriptive study using secondary data from medical records over five years (2020–2024). A total of 66 subjects were studied, with the majority being male (78.8%, n = 52) and an average age of 28.1 ± 6.5 years (range: 15–54). The largest age group was 15–34 years (47%, n = 31). Most patients were self-employed in machinery, metalwork, trade, and agriculture (45.5%, n = 30). The most common eye trauma was injury to the eyelid and adnexa (18.8%, n = 19), followed by open laceration or penetrating trauma of the eyeball (27.3%, n = 18). The primary mechanism of injury was impact by blunt or sharp objects (53%, n = 35), followed by puncture wounds from sharp objects during activities like nailing (10.6%, n = 7) and exposure to cleaning or maintenance equipment (10.6%, n = 7). Other causes included cutting activities (6.1%, n = 4), welding (6.1%, n = 4), and exposure to chemicals (4.5%, n = 3). Visual impairment was reported in most cases (66.7%, n = 44), and the same percentage required surgical intervention. Urgent measures are needed to improve awareness of workplace eye safety and implement effective prevention strategies. Occupational safety programs should include specific training on eye protection and educational campaigns to enhance workers’ understanding of risks and preventive measures for work-related eye trauma.